(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
Uzbekistan The Republic of Uzbekistan is a developing economy considering local products such as the production and practice of fidalanish shuningdek, Kyrgyzstan Kyrgyzstan Kyrgyzstan Kyrgyzstan Kyrgyzstan kyrgyzstan kymatga higmatga ega hulgan, the production of islab Kyrgyzstan kyrgyzstan and the mountain range of yurtning rivolanish. Shuningdek, a long-time industrialist striving for restoration, has the ability to innovate, accurately calculate the necessary conditions